Experimental study on adsorbing of flue gas and its application in preventing spontaneous combustion of coal - Fei Gao; Cun-Bao Deng; Xue-Feng Wang; Xue-Ming Li; Feng-Wei Dai (Adsorption Science & Technology)
We propose an experimental adsorption device, imitating the environment of a coal-mine goaf and the composition of the flue gas in Tashan Mine Power Plant. The characteristics of the coal adsorbing flue gas were studied with the atmospheric volumetric method. The factors affecting the seal of CO 2 were analyzed and the effect of power plant flue gas on fire prevention in the goaf was investigated at normal temperature and pressure. It can be inferred from the experiment that N 2 , SO 2 , and H 2 O can also reduce CO 2 adsorption capacity. The increase or decrease in pH can increase the adsorption capacity of CO 2 , which is apparently larger when the pH is decreasing than when the pH is increasing. The O 2 adsorption capacity can evidently be reduced when the power plant flue gas is injected into the goaf. The activation energy of coal burned in air is greater than that of coal burned in flue gas, indicating that the use of power plant flue gas, with N 2 and CO 2 as the main components, to replace the traditional inert gas can not only save N 2 generation cost, but also reduce the emission of greenhouse gases, while the power plant flue gas can be adsorbed by coal.